2022
DOI: 10.1021/acsnano.2c03549
|View full text |Cite
|
Sign up to set email alerts
|

Single-Particle Insights into Plasmonic Hot Carrier Separation Augmenting Photoelectrochemical Ethanol Oxidation with Photocatalytically Synthesized Pd–Au Bimetallic Nanorods

Abstract: Understanding the nature of hot carrier pathways following surface plasmon excitation of heterometallic nanostructures and their mechanistic prevalence during photoelectrochemical oxidation of complex hydrocarbons, such as ethanol, remains challenging. This work studies the fate of carriers from Au nanorods before and after the presence of reductively photodeposited Pd at the single-particle level using scattering and emission spectroscopy, along with ensemble photoelectrochemical methods. A sub-2 nm epitaxial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 89 publications
1
27
0
Order By: Relevance
“…Then, holes would appear on the surfaces of active Pd sites. [81] Subsequently, the produced holes would oxidize the OH ads species (instead of OH − ions) adsorbed on the surfaces of Pd atoms into OH radicals, followed by the cleavage of the C-C bond of neighboring ethanol molecules absorbed on the surfaces of Pd atoms by reacting with OH radicals because of its extremely strong oxidative ability. [82,83] Moreover, partial electrons transferring from Pd to Au atoms and continuous consumption of holes can in turn effectively inhibit the recombination of hot electrons and holes.…”
Section: Possible Mechanisms Of Nir-spiky Au@aupd Nps Toward Eormentioning
confidence: 99%
“…Then, holes would appear on the surfaces of active Pd sites. [81] Subsequently, the produced holes would oxidize the OH ads species (instead of OH − ions) adsorbed on the surfaces of Pd atoms into OH radicals, followed by the cleavage of the C-C bond of neighboring ethanol molecules absorbed on the surfaces of Pd atoms by reacting with OH radicals because of its extremely strong oxidative ability. [82,83] Moreover, partial electrons transferring from Pd to Au atoms and continuous consumption of holes can in turn effectively inhibit the recombination of hot electrons and holes.…”
Section: Possible Mechanisms Of Nir-spiky Au@aupd Nps Toward Eormentioning
confidence: 99%
“…Among the several mechanisms that have been reported so far for photochemical reactions, mechanisms involving energetic hot carriers (electrons and holes) generated in Au nanoparticles upon LSPR excitation have attracted special research attention in recent years. The growth rate or morphological selectivity of bimetallic structures through plasmonic-mediated synthesis has been reported, , and studies on the deposition growth of Pd and Pt by hot electron contribution have also been reported. , In addition, the growth of Au and Cu nanoparticles by SPR-based localized photothermal heating on Ag surfaces has been reported. , A mechanism in which the growth and etching of Au nanoparticles via plasmonic hot carriers is dependent on the light intensity and the concentration of HAuCl 4 has also been reported by Long et al Mukherjee et al reported that the transfer of hot electrons generated in Au nanoparticles to a H 2 molecule adsorbed on the nanoparticle surface triggered the dissociation of H 2 at room temperature . Furthermore, Kamarudheen et al reported a photoreduction mechanism based on interband charge carriers for the formation of Au@Ag core–shell structures .…”
Section: Introductionmentioning
confidence: 99%
“…The longitudinal LSPR is particularly sensitive to the AuNR aspect ratio, enabling tuning of the resonance across the visible and near-infrared . A secondary metal shell on the AuNR also impacts the LSPR response; coating AuNRs with silver (Ag) enhances their optical response and molecular detection sensitivity. , Other than Ag, deposition of catalytically active metals such as platinum (Pt) or palladium (Pd) onto AuNRs forms highly active photocatalysts. , AuNRs with Pt deposited specifically on the tips have demonstrated increased activity for the hydrogen evolution reaction compared to homogeneously Pt-covered AuNRs and other Au- and/or Pt-based nanostructures. , …”
mentioning
confidence: 99%
“…23 laser irradiation power, and substrate coupling. 11,22,24,25 However, due to the diffraction-limited spatial resolution, DFS and other optical microscopy-based techniques cannot visualize detailed structural changes to an individual AuNR. An alternative and complementary approach is liquid-phase transmission electron microscopy (LP-TEM), which can visualize in real time metal shell deposition on nanoparticles with nanometer spatial resolution.…”
mentioning
confidence: 99%
See 1 more Smart Citation